1991
DOI: 10.1002/ps.2780320213
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of permethrin for the protection of cattle against mosquitoes (diptera: Culicidae), applied as electrostatic and low pressure sprays

Abstract: Permethrin was tested for the protection of cattle against field populations of mosquitoes. Permethrin (500 ml of a permethrin 4.0 g liter-' aqueous emulsion) applied with a 'Dual-Cloud' electrostatic sprayer was effective in providing coverage of the cattle body surface of a group of four animals; 100 ml of a permethrin 5.0 g liter-' aqueous emulsion applied with a 'Dual-Cloud' electrostatic sprayer as a total body spray to a yearling heifer provided 70% or better protection from field populations of mosquito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…Although several differing formulations of permethrin were used, our results are consistent with previous studies that reported reduced mosquito, black ßy, and biting midge blood feeding from livestock treated with permethrin. Reductions in blood feeding rates of 40 Ð70% have been reported for mosquitoes (Shemanchuk et al 1991, Loftin et al 1996 to 70% or greater for black ßies (Shemanchuk and Taylor 1984) and up to 80% for biting midges (Mullens et al 2000). A similar protective effect from blood feeding by the sand ßy, Phlebotomus perniciosus Newstead, on dogs treated with deltamethrin-impregnated collars was reported by Killick-Kendrick et al (1997).…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…Although several differing formulations of permethrin were used, our results are consistent with previous studies that reported reduced mosquito, black ßy, and biting midge blood feeding from livestock treated with permethrin. Reductions in blood feeding rates of 40 Ð70% have been reported for mosquitoes (Shemanchuk et al 1991, Loftin et al 1996 to 70% or greater for black ßies (Shemanchuk and Taylor 1984) and up to 80% for biting midges (Mullens et al 2000). A similar protective effect from blood feeding by the sand ßy, Phlebotomus perniciosus Newstead, on dogs treated with deltamethrin-impregnated collars was reported by Killick-Kendrick et al (1997).…”
Section: Discussionsupporting
confidence: 50%
“…The basis for the repellent, repulsion, or anti-feeding effect of permethrin is unclear. Synthetic pyrethroids are known to have rapid effects on the nervous system of insects (Beeman 1982), with resulting irritation (Shemanchuk et al 1991, McLaughlin et al 1989, or intoxication (Mullens et al 2000), that interferes with the feeding of ßies (anti-feeding effects, Killick- Kendrick et al 1997) attracted to treated animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Options include the applied electric field between the nozzle and the nearest earthed object, the space-charge electric field effect and an induced imagecharge electric field effect (Figure 10.6) and there is often a naturally occurring electric-potential gradient (typically ~130 V/m fair-weather field) near the surface of the ground as positive polarity in the upper atmosphere induces a negative charge on the earth's surface. Shemanchuk et al (1990) reported deposition of electrostatically charged sprays on cattle to protect them from mosquitoes. Shemanchuk et al (1990) reported deposition of electrostatically charged sprays on cattle to protect them from mosquitoes.…”
Section: Deposition Studiesmentioning
confidence: 99%